Nutrigenomics: A promising frontier in chronic disease prevention - Seyed Morteza Hosseiniara; Solmaz Sadat Hosseini Zijoud (Journal of Preventive and Complementary Medicine)
Nutrigenomics, the scientific discipline that explores the complex interplay between dietary intake and gene expression, has gained significant prominence in recent years. This emerging field offers a novel framework for understanding the mechanisms underlying chronic disease development and presents a unique opportunity for implementing personalized dietary interventions aimed at disease prevention and management.This review synthesizes recent advancements in nutrigenomics research, highlighting key findings, emerging challenges, and promising future directions. A growing body of evidence illustrates the profound impact of dietary components on various aspects of human biology, including gene expression, epigenetic modifications, and cellular metabolism. These findings carry significant implications for chronic diseases such as obesity, type 2 diabetes, cardiovascular diseases, and various cancers.For example, studies have demonstrated that specific dietary patterns and individual genetic variations can influence susceptibility to these diseases. This knowledge has the potential to inform the development of personalized dietary recommendations tailored to an individual's unique genetic makeup, thereby optimizing strategies for disease prevention and treatment.However, translating these promising findings into routine clinical practice requires overcoming several critical challenges. These include the integration of diverse and complex datasets from various sources -such as genomics, metabolomics, and proteomics- the development of robust bioinformatics tools for data analysis and interpretation, and careful consideration of ethical implications, including privacy concerns and the potential for genetic discrimination.Moving forward, the integration of multi-omics approaches -encompassing a comprehensive analysis of an individual's genetic, epigenetic, metabolic, and proteomic profiles- will be crucial for advancing the field of nutrigenomics. Additionally, fostering interdisciplinary collaborations among researchers in nutrition, genetics, bioinformatics, and clinical medicine will be essential for translating research findings into effective clinical interventions.In conclusion, nutrigenomics holds immense potential to revolutionize public health strategies by enabling the development of personalized dietary interventions for disease prevention and management. By addressing current challenges and leveraging the power of multi-omics and interdisciplinary research, we can harness the potential of nutrigenomics to advance precision medicine and ultimately enhance human health and well-being.